Public participation in local governments in Bangladesh: experience, challenges and the future - Panday, Pranab Kumar (2019)
Despite constitutional guarantees of a clear separation of power between the central and local governments in Bangladesh, problems continue to lie in politicians not upholding the spirit of the decentralisation of power to the local level. This is one of the very few areas where consensus building among the ruling and opposition parties is possible, which could result in public participation in local governing processes becoming more active and meaningful than it has been to-date. The challenges involved have hindered the possibility of local governments contributing efficiently and effectively to the overall development of the country. - Reproduced.